Pengaruh Pemberian Buah Pisang Ambon Terhadap Konsistensi Feses Pada Anak Diare Usia Balita - Anita Kristianingsih; Sri Hartini Mardi Asih; Arlies Zenitha Victoria (STIKes Ibnu Sina Ajibarang, 2023)
Diarrhea is a condition of watery defecation for more than three days with or without blood and/or slime in the feces. Prolonged diarrhea for days makes children suffer from liquid and dehydration. Severe diarrhea may lead to mortality. One of the non-pharmacological efforts is to provide Ambon bananas., Cavendish bananas. This research determined the influence of Cavendish banana administration on the fecal consistency of toddlers suffering from diarrhea. This quasi-experimental research used a one-group pretest-posttest control design. The inclusion criteria were toddlers aged between 1 and 5 years old, mothers of toddlers with voluntariness to be the respondents, toddlers with diarrhea care, toddlers with a willingness to consume bananas, toddlers without banana allergies, and impatient toddlers without comorbid. The exclusion criteria were children with diarrhea before 3 days of intervention and children who did not consume all given bananas. The samples were 30 respondents taken purposive sampling. The applied instrument was the Bristol Stool Chart. The researcher administers the Cavendish banana with a dose of 100 grams, twice a day for three days. The Wilcoxon test found the influence of the Ambon banana, and Cavendish banana, on the fecal consistency of toddlers suffering from diarrhea with a p-value of 0.000, lower than 0.05. The conclusion: the administration of Ambon banana, Cavendish banana, influenced the fecal consistency of toddlers suffering from diarrhea. Recommendation: the researcher recommends the administration of consuming Ambon banana as the nursing care intervention for toddlers suffering from diarrhea.